2020
DOI: 10.1002/gps.5269
|View full text |Cite
|
Sign up to set email alerts
|

Construction and evaluation of multidomain attention training to improve alertness attention, sustained attention, and visual‐spatial attention in older adults with mild cognitive impairment: A randomized controlled trial

Abstract: Objectives We aimed to analyze the effects of multidomain attention training on alertness, sustained attention, and visual‐spatial attention in older adults with mild cognitive impairment (MCI). Design The design used in this study was a two‐arm, parallel group, double‐blind randomized controlled trial. Setting and participants The participants of the study were seventy‐eight older adults with MCI (mean age: 79.5 ± 7.9 years) from retirement centers and community housing for the elderly. Intervention The parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Abdulrahman Al-Thaqib et al in their work with cognitive brain training game "Lumosity" exhibits improvements in cognitive domains including attention and motor speed 18 . Hui-Ling Yang et al in their study on MCI adults observed better results in cognitive measures of memory, orientation and attention, while training with CogniPlus after six weeks in intervention group 19 . Ji-Su Park and colleagues also found significantly greater improvement in the MoCA, TMT-A, TMT-B , and DST-forward scores in their virtual realitybased cognitive-motor rehabilitation (VRCMR) group after six weeks of training for 30 min per day and 5 days/week 20 .…”
Section: Resultsmentioning
confidence: 94%
“…Abdulrahman Al-Thaqib et al in their work with cognitive brain training game "Lumosity" exhibits improvements in cognitive domains including attention and motor speed 18 . Hui-Ling Yang et al in their study on MCI adults observed better results in cognitive measures of memory, orientation and attention, while training with CogniPlus after six weeks in intervention group 19 . Ji-Su Park and colleagues also found significantly greater improvement in the MoCA, TMT-A, TMT-B , and DST-forward scores in their virtual realitybased cognitive-motor rehabilitation (VRCMR) group after six weeks of training for 30 min per day and 5 days/week 20 .…”
Section: Resultsmentioning
confidence: 94%
“…Beyond SENIOR, ACTA features a number of new technological strategies that will increase the customization of the therapy, now based on the real-time neural signature of the individual's attention, and the quantitative monitoring of attention and memory abilities all throughout the course of the rehabilitation program. Moreover, ACTA will provide answers to the relationship between such an advanced cognitive and motor training and the brain networks changes [66,73]. This will open up the way to further optimize the training strategies (both in the "Nudge theory" and in the NFB).…”
Section: Discussionmentioning
confidence: 98%
“…Bottiroli S. et al (2017) used the MoCA test subscales (executive functions, working memory, visual-spatial processing, language and orientation) as effectiveness criteria for cognitive skills training in elderly people in the 3D virtual reality platform Smart Aging [29].The use of data from the MoCA subscales allowed the authors to conclude that this virtual platform appears to be a good tool for assessing primarily executive functions, working memory and visual-spatial processes [29]. A double-blinded randomized control trial of multidomain attention training for alertness, sustained attention and visual-spatial attention in older adults with mild cognitive impairment (MCI) was performed [30]. Some of the indicators of the effectiveness of such training were the subscales of the MoCA test (sustained attention and visual-spatial attention).…”
Section: Discussionmentioning
confidence: 99%